2018
DOI: 10.3390/f9070382
|View full text |Cite
|
Sign up to set email alerts
|

Climate Sensitive Tree Growth Functions and the Role of Transformations

Abstract: The aim of this study is to develop climate-sensitive single-tree growth models, to be used in stand based prediction systems of managed forest in Switzerland. Long-term observations from experimental forest management trials were used, together with retrospective climate information from 1904 up to 2012. A special focus is given to the role of transformation of modelling basal area increment, helping to normalize the random error distribution. A nonlinear model formulation was used to describe the basic relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Because of this, climate variables that are often expected to be influential including mean temperature, maximum temperature, and total annual precipitation (Subedi and Sharma, 2013;Manso et al, 2015), did not always perform well in climate-based growth models. However, the interacting effects of climate variables on the tree growth are largely influenced by the individual tree status, stand level competition and site quality while interpreting the biological growth (Zell, 2018). In our study also, change in the coefficient magnitudes for individual tree status, stand age, and stand level competition indicates that climate variables also influence the biological growth pattern of this species.…”
Section: Forestrymentioning
confidence: 53%
See 2 more Smart Citations
“…Because of this, climate variables that are often expected to be influential including mean temperature, maximum temperature, and total annual precipitation (Subedi and Sharma, 2013;Manso et al, 2015), did not always perform well in climate-based growth models. However, the interacting effects of climate variables on the tree growth are largely influenced by the individual tree status, stand level competition and site quality while interpreting the biological growth (Zell, 2018). In our study also, change in the coefficient magnitudes for individual tree status, stand age, and stand level competition indicates that climate variables also influence the biological growth pattern of this species.…”
Section: Forestrymentioning
confidence: 53%
“…This might be because most of the studies have been formulated either on tree-ring chronologies or on annual measurement data where climate variables are regressed against annual growth (Biondi, 2000;Jump et al, 2006;Chhin et al, 2008;Duchesne et al, 2012;Foster et al, 2015). However, Zell (2018) has recently investigated the effects of climate on growth from multi-year periodic measurements of forests in Switzerland. Additionally, the growth models in some of these studies are already linear in form of their arguments (Subedi and Sharma, 2013;Manso et al, 2015) and added climate variables performed better than was the case with our nonlinear model.…”
Section: Climate Based Abag Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong vessel plasticity from M. schiedeana, given drought events ( Figure 4), enhances the statement of its need for specific microclimatic. Rodríguez-Ramírez et al [32] found that Mexican beech trees develop similar vessel trait adjustments, which may indicate that this forest type may be very sensitive to drought and thus susceptible to climate change [17,63,64]. On the other hand, M. vovidesii appears to show resilience to climatic variations such as strong DY, this is seen as a response to climatic variations such as strong DY (Figure 4).…”
Section: Discussionmentioning
confidence: 90%
“…Climate signals such as precipitation (e.g., rain, mist, fog and cloud water), temperature and/or droughts regulate the growth of TMCFs' tree species [15,16]. Dendroecology allows us to identify climatic processes across time and can be used to reconstruct past local and regional climates [9,16,17]. In this context, one of the most important advances in dendrochronological studies has been the additional focus on anatomical features such as vessel traits and/or tree-ring anatomy [13,18,19].…”
Section: Introductionmentioning
confidence: 99%